Risk factors for severe Rift Valley Fever infection in Kenya, 2007 - Anyangu, A.S.; Gould, L.H.; Sharif, S.K.; Nguku, P.M.; Omolo, J.O.; Mutonga, D.; Rao, C.Y.; Lederman, E.R.; Schnabel, D.; Paweska, J.T.; Katz, M.; Hightower, A.; et al. (American Society of Tropical Medicine and Hygiene, 2010)
A large Rift Valley fever (RVF) outbreak occurred in Kenya from December 2006 to March 2007. We conducted a study to define risk factors associated with infection and severe disease. A total of 861 individuals from 424 households were enrolled. Two hundred and two participants (23%) had serologic evidence of acute RVF infection. Of these, 52 (26%) had severe RVF disease characterized by hemorrhagic manifestations or death. Independent risk factors for acute RVF infection were consuming or handling products from sick animals (odds ratio [OR] = 2.53, 95% confidence interval [CI] = 1.78–3.61, population attributable risk percentage [PAR%] = 19%) and being a herdsperson (OR 1.77, 95% CI = 1.20–2.63, PAR% = 11%). Touching an aborted animal fetus was associated with severe RVF disease (OR = 3.83, 95% CI = 1.68–9.07, PAR% = 14%). Consuming or handling products from sick animals was associated with death (OR = 3.67, 95% CI = 1.07–12.64, PAR% = 47%). Exposures related to animal contact were associated with acute RVF infection, whereas exposures to mosquitoes were not independent risk factors.